Some species of meliolacea fungi from the state of Mato Grosso-Brasil - Vélez Zambrano, Sergio Miguel (2017)
The objective of this research was to identify and describe some species of Meliola (Meliolales/Ascomycetes/Ascomycota) linked to wild plants from the Brazilian Cerrado. We analyzed samples collected at the Pelicano del Parque Estatal Serra Ricardo Franco farm, located in Vila Bela da Santíssima Trindade on the border with Bolivia, and in Barra do Garças, both sites located in the State of Mato Grosso. Following the display of vegetative and reproductive fungi structures, we mounted glass sheets containing lactoglycerol, which were sealed with varnish for analysis through a stereoscope and light microscope. We identified a total of 5 species of Meliola as follows: M. alibertiae en Alibertia edulis, M. desmodii–laxiflori y M. stizolobii var. eriosematis en Desmodium spp., M. kernii en Casearia sp. Meliola voacangae en Aspidosperma nobile. We identified each species based on the host plant, ascoma morphology, shape and dimension of ascospores, ramification of hyphae, distribution of appressors and sperm hyphipods in the hyphae.